The role of relational coordination in the relationship between high-performance work systems (HPWS) and organizational performance. Issue 4 (2nd December 2019) - Siddique, Muhammad; Procter, Stephen; Gittell, Jody Hoffer
Abstract : Purpose: The purpose of this paper is to look at the role relational coordination might play in understanding the relationship between high-performance work systems (HPWS) and organizational performance. Design/methodology/approach: Research was conducted in a large financial services provider in Pakistan. Across 120 branches of the bank, data on relational coordination and on the practices making up HPWS were obtained from employees by means of a questionnaire survey. Data on branch-level performance were obtained independently of this, from the bank itself. Findings: Analysis shows relational coordination to be a mediating variable between HPWS and branch performance. Relational coordination is also a mediating variable for each of the three component parts of HPWS: ability-enhancing, motivation-enhancing and opportunity-enhancing HR practices. Practical implications: These results have important implications from two points of view. From the point of view of relational coordination, they show how the concept might apply in a previously under-researched sector, and also how relational coordination might act as a mediator for HR practices other than those aimed directly at enhancing employee opportunities. Breaking down HPWS into its component parts suggests that individual employee ability and motivation might also play a role. Originality/value: This suggests that the ability-motivation-opportunity model needs to place greater emphasis on opportunity, and also that more account needs to be taken of the structural aspect of work – in particular, the degree of interdependence.